Obsidian treatment technology in the Lengyel culture - Lucia Popovičová; Noémi Beljak Pažinová (Documenta Praehistorica)
The article examines the treatment technology of the obsidian chipped stone industry, which, like the other findings, is mostly obtained from the major feature B15. The remains of an oven with a dome-shaped vault were also discovered inside it. Obsidian has an extremely high ratio among raw materials used in tool manufacturing at the monocultural site, accounting for 62% of the assemblage. All phases of its processing are present, allowing the reconstruction of technology. Obsidian is commonly used in the Lengyel culture sites in south and southwest Slovakia, but it is usually found in smaller quantities because it is a raw material obtained from a considerable distance. Until now, the more abundant assemblages have received insufficient evaluation in Slovakia. Kiarov is distinguished by the presence of miniature cores, which were utilized primarily to produce tiny bladelets, likely used as parts of more complex tools. In addition to obsidian, Tevel-type flint, limnosilicite, and silicite from the Kraków-Czêstochowa Jurassic were used in the manufacture of tools. These raw materials yielded larger blades. The Kiarov-Veľké ortovisko site demonstrates the different usage of several raw materials.